Mass balance and metabolism of Z-215, a novel proton pump inhibitor, in healthy volunteers. (3rd October 2018) - Toda, Ryoko; Miyagawa, Tomoharu; Masuda, Yuka; Hoshino, Yusuke; Yoshii, Kazuyoshi; Hirayama, Masamichi; Shibuya, Minaka; Kawabata, Yoshihiro
Abstract: The human mass balance of [ 14 C]Z-215, a novel proton pump inhibitor, was characterised in six healthy male volunteers following single oral administration of [ 14 C]Z-215 (20 mg, 3.7 MBq) to determine the elimination pathway of Z-215 and the distribution of its metabolites in plasma, urine, and faeces (NCT02618629). [ 14 C]Z-215 was rapidly absorbed, with a Cmax of 434 ng/mL at 0.38 h for Z-215 and 732 ng eq./mL at 0.5 h for total radioactivity. Means of 59.61% and 31.36% of the administered radioactive dose were excreted in urine and faeces, respectively, within 168 h post-dose. The majority of the dose was recovered within 24 h in urine and 96 h in faeces. Unchanged Z-215 was excreted in urine at trace levels but was not detected in faeces. The main components in plasma were Z-215 and Z-215 sulphone, accounting for 29.8% and 13.3% of the total circulating radioactivity, respectively. Additionally, Z-215 was metabolised through oxidation, reduction and conjugation. Our in vitro Z-215 metabolism study showed that the major isozyme contributing to the oxidation of Z-215, including the formation of Z-215 sulphone, was CYP3A4. In conclusion, Z-215 is well absorbed in humans and primarily eliminated via metabolism, where CYP3A4 plays an important role.